2020
DOI: 10.3390/ma13132997
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hybrid Carbon Materials Consisting of N-Doped Microporous Carbon and Amorphous Carbon Nanotubes

Abstract: The N-doped hybrid carbon materials containing amorphous carbon nanotubes (ACNTs) were obtained by free growth of a polymer at 200 °C. The improvement of electrical conductivity was achieved by a final carbonization at 600–800 °C under the flow of nitrogen. The microstructure of ACNT/N-doped hybrids was characterized using a transmission electron microscope and X-ray diffusion. Furthermore, their elemental composition was measured using energy-dispersive X-ray spectroscopy and an elemental analyzer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Moreover, the fitting results ( Figure S1 ) further displayed that C1s could be decomposed into amorphous carbon, C=C, and C-OH in both SLA-ZrP0.5 and SLA-ZrP0.7. Previous study has revealed that the peaks of amorphous carbon and C=C were associated with the hybridization of carbon sp2, 43 which were also closely related to the appearance of D and G bands in the resulting Raman ( Figure 3B ). The C-OH in samples might be caused by environmental contamination.…”
Section: Resultsmentioning
confidence: 53%
“…Moreover, the fitting results ( Figure S1 ) further displayed that C1s could be decomposed into amorphous carbon, C=C, and C-OH in both SLA-ZrP0.5 and SLA-ZrP0.7. Previous study has revealed that the peaks of amorphous carbon and C=C were associated with the hybridization of carbon sp2, 43 which were also closely related to the appearance of D and G bands in the resulting Raman ( Figure 3B ). The C-OH in samples might be caused by environmental contamination.…”
Section: Resultsmentioning
confidence: 53%
“…The XPS survey spectrum of NMWCNTs (Figure S5) confirms the existence of the elements, carbon, nitrogen, and oxygen. The de‐convoluted C 1s spectrum shows that the C is present in five forms as C=C, C−C, C−O/C−N, and C=O at the binding energy values of 284.5, 284.8, 285.4, and 286.6 eV [55,56] . The N 1s spectrum is de‐convoluted to four peaks representing four types of N species corresponding to pyridinic N (399.0 eV), pyrrolic N (400.0 eV), graphitic N (401.2 eV), and oxidized N (406.7 eV) in the NMWCNTs [57,58] .…”
Section: Resultsmentioning
confidence: 99%
“…The de-convoluted C 1s spectrum shows that the C is present in five forms as C=C, CÀ C, CÀ O/CÀ N, and C=O at the binding energy values of 284.5, 284.8, 285.4, and 286.6 eV. [55,56] The N 1s spectrum is de-convoluted to four peaks representing four types of N species corresponding to pyridinic N (399.0 eV), pyrrolic N (400.0 eV), graphitic N (401.2 eV), and oxidized N (406.7 eV) in the NMWCNTs. [57,58] The spectrum shows the highest intensity for the graphitic N which confirms the successful doping of N in the MWCNTs.…”
mentioning
confidence: 99%
“…The Raman spectrum of the C-Flax sample ( Figure 1 c) showed two distinct peaks indexed as D-band (1334 cm –1 ) and G-band (1596 cm –1 ). The presence of the first was related to internal structural defects, edge defects, and dandling bonds (i.e., disorder-induced defects of graphitic carbon [ 35 ]), and the amorphous nature of carbon [ 36 ], while the latter came from the stretching mode of symmetric C–C bonds [ 37 ]. The D-band (ID) vs. G-band (IG) ratio was 1.21, which indicated a large number of structural disorders and a partially graphitic structure of this sample.…”
Section: Resultsmentioning
confidence: 99%
“…phitic carbon [35]), and the amorphous nature of carbon [36], while the latter came from the stretching mode of symmetric C-C bonds [37]. The D-band (ID) vs. G-band (IG) ratio was 1.21, which indicated a large number of structural disorders and a partially graphitic structure of this sample.…”
Section: Chemical and Morphological Characterizationmentioning
confidence: 89%